The Chaperoning and Assistance Roles of the HIV-1 Nucleocapsid Protein in Proviral DNA Synthesis and Maintenance - Bampi, Carole; Jacquenet, Sandrine; Lener, Daniela; Decimo, Didier; Darlix, Jean- L. (Current HIV Research, 2004)
In the following three sections we will briefly review the seminal roles of the HIV-1 nucleocapsid protein NCp7 in the fate of the HIV-1 full length RNA from genomic RNA in a dimeric form to the proviral DNA. Emphasis will be given to the mechanisms of NC-directed assistance to the genomic RNA and reverse transcriptase in the course of proviral DNA synthesis and to DNA integrity at the end of the polymerization process, and to the NC-assisted repair and recombination reactions fueling the viability and variability of the virus.
Keywords: proviral dna maintenance